Pengembangan E-LKPD Berbasis Etnomatematika Pada Materi Pola Bilangan - ALYA NUR SAADAH; Selvi Loviana (Prodi Pendidikan Matematika STKIP Persada Khatu;istiwa Sintang, 2026)
This study aims to develop an ethnomathematics-based Electronic Student Worksheet (e-LKPD) on number pattern material for eighth-grade junior high school students as a form of technology integration in learning. The e-LKPD integrates cultural elements, such as the Gordang Sambilan musical instrument and the Tongkonan traditional house, to create more contextual and meaningful learning experiences. This study employed a 4D development model consisting of defining, designing, developing, and disseminating stages. The validation results from material and media experts indicated that the developed e-LKPD was categorized as highly valid, while student responses showed that it was highly practical. The product was tested on a limited scale at SMP Negeri 6 Metro. Therefore, the developed ethnomathematics-based e-LKPD is feasible to be used as a learning medium to support students in understanding number pattern concepts more meaningfullyKeyword: e-LKPD, Ethnomathematics, Mathematics.